Cost Analysis of Health Examination Screening Program for Ischemic Heart Disease in Active-Duty Military Personnel in the Middle-Income Country - Radoje Simic; Radoje Simic; Nenad Ratkovic; Nenad Ratkovic; Viktorija Dragojevic Simic; Viktorija Dragojevic Simic; Zorica Savkovic; Mihajlo Jakovljevic; Mihajlo Jakovljevic; Vitomir Peric; Milena Pandrc; Nemanja Rancic; et al. (Frontiers Media S.A., 2021)
Cardiovascular diseases, including ischemic heart disease, are the most common causes of morbidity and death in the world, including Serbia, as a middle-income European country. The aim of the study was to determine the costs of preventive examinations for ischemic heart disease in active-duty military personnel, as well as to assess whether this was justified from the point of view of the limited health resources allocated for the treatment of the Republic of Serbia population. This is a retrospective cost-preventive study which included 738 male active-duty military personnel, aged from 23 to 58. The costs of primary prevention of ischemic heart disease in this population were investigated. Out of 738 subjects examined, arterial hypertension was detected in 101 subjects (in 74 of them, arterial hypertension was registered for the first time, while 27 subjects were already subjected to pharmacotherapy for arterial hypertension). Average costs of all services during the periodic-health-examination screening program were €76.96 per subject. However, average costs of all services during the periodic-health-examination screening program for patients with newfound arterial hypertension and poorly regulated arterial hypertension were €767.54 per patient and €2,103.63 per patient, respectively. Since periodic-health-examination screening program in military personnel enabled not only discovery of patient with newfound arterial hypertension but also regular monitoring of those who are already on antihypertensive therapy, significant savings of €690.58 per patient and €2,026.67 per patient can be achieved, respectively. As financial resources for providing health care in Serbia, as a middle-income country, are limited, further efforts should be put on screening programs for ischemic heart disease due to possible significant savings.